NARRATIVE OF KURZEME IN MODERN CHILDREN’S NON-FICTION BOOKS BY LATVIAN AUTHORS - Okuņeva, Sandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The aim of the article is to characterize the peculiarities of regional literature in a specific type of children’s literature – non-fiction books. The research focuses on the analysis of the narrative of Kurzeme, the cultural and historical region of Latvia, in the books for children by four contemporary Latvian authors – Gundega Sēja, Vitauts Ļūdēns, Valdis Klišāns and Pēteris Blūms. Using the methodology of narrative and semiotic analysis, the research has identified the main trends in the representation of Kurzeme in the creation of content and story. In the books, the writers have included information about geography, the most important natural and cultural-historical objects, historical persons and events, the peculiarity of the language, as well as certain traditions. The formation of Kurzeme narrative is dominated by a dialogue between a child and an adult, with the adult playing the role of a wise companion, as well as the technique popular in travel literature – "story within a story". The study shows the need to continue academic discussions on identifying the most appropriate term for non-fiction books in the research of Latvian children’s literature and allows to conclude that non-fiction books about Latvia and Kurzeme written by contemporary Latvian authors can be considered as important revealers of regional color.